Ethiopia's growth and transformation plan: A computable general equilibrium analysis of alternative financing options - Engida, Ermias; Tamru, Seneshaw; Tsehaye, Eyasu; Debowicz, Dario; Dorosh, Paul A.; Robinson, Sherman (International Food Policy Research Institute, 2011)
Under the Plan for Accelerated and Sustained Development to End Poverty (PASDEP), implemented from 2005/06 to 2009/10, Ethiopia achieved rapid economic growth and laid a foundation for future growth by making substantial investments in infrastructure and human capital. The Growth and Transformation Plan (GTP) for 2010/11-2014/15, Ethiopia's new five year plan, sets even higher growth and investment targets. This paper analyzes these new GTP investment and growth targets using a Computer General Equilibrium (CGE) model of the Ethiopian economy to assess the implications of the plan on sectoral growth and household incomes. The analysis of the GTP investment plan indicates that achieving its high growth targets will require rapid increases in total factor productivity and large-scale mobilization of domestic and foreign savings. The 4.9 percent annual Total Factor Productivity (TFP) growth needed to reproduce the high Gross Domestic Product (GDP) growth under PASDEP (2005/06 to 2009/10) or to continue this growth into the future is very high in comparison to those that have been achieved in other fast-growing economies such as India, China, and Indonesia. Achieving the GTP target GDP growth rates requires even higher TFP growth: by 5.8 and 7.6 percent per year respectively in the medium and high growth GTP scenarios. To some extent, some of this productivity growth could be achieved through reduced underemployment. Nonetheless, these results suggest that the projected GDP growth outcomes are very optimistic.